SOSIALISASI CORETAX DAN PAJAK PENGHASILAN PASAL 21 DENGAN TARIF EFEKTIF RATA-RATA PADA PEGAWAI UPT PUSKESMAS JUMAPOLO" - Rizki Fajar; Suhesti Ningsih; M. Hasan Ma'ruf (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The purpose of this community service activity is to improve the understanding of employees at the Jumapolo Health Center Technical Implementation Unit, especially regarding the calculation of Income Tax Article 21 Average Effective Rate and socialization of the use of the Coretax tax reporting application. Tax regulations and the implementation of the Coretax application have caused several changes in the mechanisms of tax deductions, deposits, and reporting in the government environment, especially at the Jumapolo Health Center Technical Implementation Unit. The method of implementing this activity is the socialization of the Coretax application and simulation with all Health Center employees, as well as conducting discussions with related parties for Article 21 Income Tax deductions and conducting tax calculation simulations in accordance with the latest provisions. The results of this activity indicate an increase in the understanding of employees regarding the use of the Coretax application in reporting Annual Tax Returns and implementing the latest tax regulations regarding Article 21 Income Tax. The employees also interact with each other and provide positive feedback on the implementation of this activity and hope that in the future there will be further assistance related to technical obstacles in the implementation of the tax reporting application and the practice of tax regulations..